Effect of two concentrate levels at the beginning of lactation on milk production and reproductive efficiency - Paiva, João Alberto de Jesus; Cruz, Geraldo Maria da; Carvalho, Mauro Ribeiro de; Neto, José Lobato; Moreira, Homero Abílio (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was conducted at the "Centro Nacional de Pesquisa de Gado de Leite"/EMBRAPA, utilizing 24 crossbred Holstein-Zebu cows, to test the following treatments: A) feeding regimen calculated to supply the maintenance requirements of crude protein (CP) and total digestible nutrients (TDN) of a 500 kg dairy cow plus 120% of the requirements of these nutrients for an estimated milk production of 12 kg/day during the first twelve weeks of lactation; B) feeding regimen calculated to supply the maintenance requirements of CP and TDN, plus 85% of the requirements of these nutrients for milk production during the same period of lactation. After this period, all 24 cows were fed according to the National Research Council (1978) standards, to the end of lactation. Milk production was higher (P < 0.05) and weight loss was lower (P < 0.01) in treatment A than in treatment B, during the first twelve weeks of lactation. There were no differences in production or composition of milk from day 85th to the end of lactation period. The interval from parturition to first ovulation was higher (P < 0.05) and the calving interval shorter (P < 0.05) in treatment A than in treatment B. Crossbred dairy cows should be fed according to National Research Council (1978) standards.